Dictatorship - Connolly, Sean J. (Systems of government, 2017)
"Describes what a dictator is, how he or she takes over a country, and what it is like to live under such a regime. The history of how dictatorships have evolved, the rise and fall of dictators, and the future of dictatorships are examined." -- Provided by publisher